ANALYSIS OF FACTORS AFFECTING PROPERTY LAND RENTAL VALUE FOR TELECOMMUNICATIONS TOWERS (Case Study on Property Land Rental Value for Telecommunications Towers in the Binjai City Region) - Muhammad Febrian; Sugiharto Pujangkoro; Arlina Nurbaity Lubis (Bajang Institute, 2023)
The purpose of this research is to analyze of factors affecting property land rental value for telecommunications towers, case study on property land rental value for telecommunications towers in the Binjai City Region. This research is a quantitative descriptive research. The location of the research object is in Binjai City, North Sumatra Province in 2022 which is spread over 5 sub-districts namely Binjai City, North Binjai, South Binjai, West Binjai, and East Binjai. The population in this sample is the owners of property land rental for telecommunications towers in the Binjai City Region with a total of 59 owners. The sample used in this study is saturated sampling. So that will be used as a sample in this study is the entire population, namely the owners of property land rental for telecommunications towers in the Binjai City Region as many as 59 owners. A common technique used to analyze the relationship between two or more variables is regression analysis. The results show that type of telecommunications towers has a positive and significant effect on property land rental value for telecommunications towers. Population density has a positive and significant effect on property land rental value for telecommunications towers. Road access to location has a positive and significant effect on property land rental value for telecommunications towers. Availability of electrical energy has a positive and insignificant effect on property land rental value for telecommunications towers.